Editorial: optimal dose of carvedilol in portal hypertension…nearly there. Issue 9 (11th April 2018) - Tripathi, D.; Stanley, A. J.
Abstract : Linked Content This articel is linked to Schwarzer et al and Reiberger and Ferlitsch papers. To view these articles visithttps://doi.org/10.1111/apt.14576 andhttps://doi.org/10.1111/apt.14614 .